Pengaruh Multimedia Presentasi (Ppt) dan Metode Manyanyi dalam Penguasaan Kosa Kata Bahasa Arab - Nia Kurniawati (Program Pascasarjana UIN Sultan Maulana Hasanuddin Banten, Jalan Jenderal Sudirman No. 30, Serang - Banten 42118, 2022)
The learning process that has taken place so far has not received satisfactory learning outcomes, as evidenced by the learning outcomes that are still below the minimum completeness criteria (KKM). This indicates a problem in the learning process. These problems can come from teachers, students, and infrastructure in schools that support the learning process. Problems that come from students include: low student learning outcomes in Arabic subjects, lack of student interest in learning Arabic, and students' assumption that Arabic is difficult to learn. Meanwhile, teacher problems can be caused by inappropriate use of learning methods and/or learning media. This study aims to analyze the effect of using multimedia presentations and singing methods in improving Arabic vocabulary mastery at Mts Attoyyibiyyah Cikande Serang Banten. This quantitative research uses the Ex Post Facto method based on the nature of this study including a causal associative research design, namely knowing the relationship between the application of multimedia presentation and singing methods with the dominance of Arabic vocabulary. This study uses correlational techniques to determine trends and collect data needed to be carried out, in this study using the questionnaire method and the test method. In the questionnaire method, the questionnaire is used as a data collection tool that has previously been tested for validity and reliability. The test method also uses questions that will be tested for validity and reliability first. Data collection tools that have previously been tested for validity and reliability. The test method also uses questions that will be tested for validity and reliability first. The results of the study are: the application of multimedia presentations and singing methods have an effect on increasing Arabic vocabulary mastery.